Prevalence of work-related burnout and associated factors among police officers in central Gondar zone, Northwest Ethiopia, 2023 - Bezie, Anmut Endalkachew; Getachew Yenealem, Dawit; Asega Belay, Azanaw; Bitew Abie, Alebachew; Abebaw, Tadiwos; Melaku, Christian; Mamaye, Yimer; Hailu Tesfaye, Amensisa (Frontiers in Public Health, 2024)
Introduction Work-related burnout is a state of physical and psychological fatigue and exhaustion resulting from chronic workplace stress related to work. The police workforce is vulnerable to this psychosocial hazard, which affects service delivery by police workers. However, there is little evidence about the prevalence of work-related burnout and associated factors among police officers in Ethiopia. Therefore, this research investigated the prevalence and predictor variables of work-related burnout among police officers in central Gondar zone, Northwest Ethiopia, 2023. Methods An institution-based cross-sectional study was carried out from April 12 to May 12, 2023. A sample of 633 police officers was recruited through multistage random sampling techniques. To measure work-related burnout, a standardized, self-administered Copenhagen Burnout Inventory was used. To enter the collected data, EpiData V 4.6 and to analyze SPSS V 26 were used. To examine the association between work-related burnout and its predictor variables, both bivariable (p < 0.2) and multivariable (<0.05) logistic regression analyses were performed, and statistical significance was established via multivariable logistic regression. Results The response rate in this study was 96.05% (n = 608). The majority, 452 (74.3%) of the police officers, were male; the median (IQR) age of participants was 28. In the past six months, 45.7% of the police officers had experienced work-related burnout (n = 278). Being female, having a high job demand, having a high level of organizational police stress, having a moderate level of operational police stress, having a high level of operational police stress, experiencing job dissatisfaction, and sleeping troubles were risk factors significantly related to the occurrence of work-related burnout among police officers. Conclusion According to this study, a significant number of police officers suffer from burnout due to their work. Police officers’ work-related burnout was found to be influenced by factors such as sex, job demands, job satisfaction, workplace stress, organizational police stress, and sleeping troubles. To address this problem, improving the handling of work pressure, developing a stress management program, finding joy at work by improving interpersonal relationships and working conditions, offering support and inspiration to female police officers, and ensuring sufficient and restful sleep are advised.